Terrestrial Analogues to Mars and the Moon:: Canada’s Role - Osinski, Gordon; Léveillé, Richard; Berinstain, Alain; Lebeuf, Martin; Bamsey, Matthew (Geoscience Canada, 2006)
Terrestrial analogues are places on Earth that approximate, in some respect, the geological, environmental and putative biological conditions on a particular planetary body, either at the present-day or sometime in the past. Analogue studies are driven by the need to understand processes on Earth in order to interpret and groundtruth data sent back from Mars and other planetary bodies by unmanned orbiters and rovers. This presents an ideal opportunity to further collaboration between the solid earth and planetary science communities in Canada and elsewhere. Analogue environments also provide a critical locale for optimizing exploration requirements and strategies for future manned missions to the Moon and Mars. The ideal geography and climate, a wide diversity of analogues sites, and a history of analogue activities, ensures that Canada can play a leading role in the expanding international use of terrestrial analogues sites.